Kontrola udzielania zamówień publicznych a nadzór w materialnym prawie administracyjnym - Horubski, Krzysztof (Wydawnictwo Naukowe UAM, 2015)
The article evaluates the provisions concerning control of public procurement procedures carried out by the President of the Public Procurement Office in light of the current concepts of supervision in the theory of administrative law and public business law, and particularly the current regulatory supervision. The underlying reason for formulating the research problem was the fact that the supervision com petences of the President of the Public Procurement Office are linked to other legal means available to the President and that in the event of a negative outcome of such supervision a direct or indirect inﬂuence may be exerted on the legal situation of the contracting authority. The above link is responsible for subsequent activities of the central government administration authority which cannot be seen solely as an examination of the behaviour of the controlled entity for the purpose of determining compliance or lack of compliance with the prescriptive standard arising from the provisions of the Public Procurement Law. The very option of awarding an administrative monetary penalty to a contracting authority or the exclusive, as a rule, capacity of bringing an action in the common law court for invalidation of a public contract entered into in breach of the provisions of the Law allows to conclude that this sequence of legal actions may be qualiﬁed as supervision in substantive administrative law. A supervisory impact on the contracting authority in the form of legal means mentioned above becomes even more prominent when combined with a supervision performed prior to the conclusion of a public procurement contract when a correction of the result of the procurement procedure is still possible so that it is compliant with the provisions of the public procurement law.
Control of public procurement procedures and supervision in substantive administrative law
Keywords: supervision in substantive administrative law; control of public procurement procedures; President of the Public Procurement Office; previous control; ad hoc control